Implementasi Kebijakan Uji KIR Gratis di UPT Pengujian Kendaraan Bermotor Kabupaten Gresik - Farhana, Yustanti Aprinda; Maharani, Shinta Aurellia; Purwanto, Regina Maulidya Putri; Ramadhan, Roif Rizaly (VISA: Journal of Vision and Ideas, 2025)
Gresik Regency is the region with the densest transport vehicle traffic in East Java because it is one of the large industrial centers. With this, all loaded vehicles operated on public roads are required to have their vehicles tested periodically and recorded in the KIR book. The Gresik Regency Transportation Service has implemented a free KIR test starting January 2024 and the testing stages are in accordance with the applicable SOP. This research aims to find out how the free KIR test policy has been implemented by the Gresik Regency Transportation Service. The method used in this research is descriptive with a qualitative approach. The results of this research include the implementation of the Free KIR test policy at the Gresik Regency Motor Vehicle Testing UPT using implementation theory from Ripley and Franklin (1986), which includes compliance, smooth implementation of routines and functions and the realization of the desired performance. The results of this research show that the free KIR test policy has been implemented in Gresik Regency, but has not yet shown significant results. This is because people are still reluctant to test their vehicles.